An Observational Study on Medicolegal Evaluation of Cause of Death in Unidentified Cadavers: An Autopsy Based Prospective Study at SMS Hospital, Jaipur During 2023-24 - Shweta Goel; R.K. Punia; Surya Bhan Kushwaha (Indian Journal of Forensic Medicine and Pathology, 2025)
Background: Identifying unknown dead bodies is an essential part of forensic medicine and plays a major role in both legal and humanitarian matters. In urban areas, where migration and homelessness are common, the number of unidenti𿿿edbodies is increasing. These cases present serious challenges in terms of medicolegal procedures and public health responsibilities. Aim: To study the demographic and medico-legal pro𿿿le of unidenti𿿿eddeadbodies at SMS Hospital, Jaipur, including cause and manner of death, seasonal trends, and identi𿿿cation methods. Methods: This hospital-based observational study was conducted over one year, from October 2023 to November 2024 at Mortuary Department of Forensic Medicine, S.M.S. Medical College and Hospitals. Out of 5052 total autopsies, 718 were categorized as unknown, and 120 unidenti𿿿ed bodies were selected for detailedanalysis. Data were collected using police inquest reports, autopsy𿿿ndings, and tructured proforma. The data were analysed using SPSS version 30. Observation & Results: Out of 120 unidenti𿿿ed bodies, 84.2% ere male. Most were aged between 31 to 50 years. Respiratory failure (38.3%) was the leading cause of death, followed by head injury (20%) and haemorrhagic shock (18.3%). Natural deaths made up 49.2%, and accidental deaths accounted for 40.8%. Identi𿿿able eatures like tattoos or scars were seen in only one-third of cases. DNA samples, mostly teeth, were preserved in over 90% of cases. A seasonal rise in deaths was seen during summer. Most bodies were found in public places, and 83.3% were disposed of within two weeks of recovery.Conclusion: The study highlights the urgent need for improved identi𿿿cationsystems, better forensic tools, and coordination between government departments. It also suggests welfare programs for vulnerable populations to reduce the number of unidenti𿿿ed deaths in urban areas.